Exploring Language Style in Makassar Cultural Tourism - Ratnawati Ratnawati; Rosmiaty Rosmiaty; Nurfaizah Nurfaizah (ELT Worldwide: Journal of English Language Teaching, 2021)
The purpose of this study is to analyze about language style of Makassar local tourism which tried to find out the kinds of language style that are mostly used in Makassar local tourism. This research focused on Matin Joos’ theory which discussed about language style. Then, it was analyzed by using descriptive approach. The research used six videos on youtube  as the instrument to find out more valid data. The result of the study was that Formal style is mostly used by tourist in within conversation the authors found five times, followed by casual style found in fourth, casual style only once, and intimate style twice. This study provides insights into the language styles neccessary to communicate with foreigners which can be a source of material for teaching english to tourism students.